Reading strategies of bachelor of education (teaching english as a second language) students : a case study of UNISEL undergraduates - Sri Hariaty bt Md Salleh (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2007)
Students’ level of understanding while reading relies much on the strategies exploited during the session. Not only do they affect students’ comprehension of the text, they also determine students’ academic achievement at large. This study aims to uncover reading strategies of students at tertiary level and addresses four research questions: (1) What are the reading strategies of good students? (2) What are the reading strategies of average students? (3) What are the reading strategies of poor students? (4) Are there significant differences in the use of strategies between these three groups? Seventy-two undergraduate TESL students were chosen as the sample for this study. These students, based on their academic performance were grouped as good, average and poor students. A 32-item questionnaire was developed; the data from the questionnaire were analyzed using descriptive and inferential statistics. Findings of this study establish that some or other reading strategies were generally applied by the three groups of students. Good students mainly used effective strategies such as starting the reading activity with good pre-reading strategies, followed by successful monitoring during and after reading. Meanwhile, average students are found to be average readers who used reasonable pre-reading strategies but were involved in rote learning in which ineffective while-reading strategies caused a lot of repetition in reading. Poor students, on the other hand, demonstrated irregular use of all strategies: pre-reading, while-reading and post-reading. The researcher thus recommends that reading strategies be taught to students to enable them in becoming more autonomous in learning.